Holmium: yttrium-aluminum-garnet laser with Moses: does it make a difference?. Issue 3 (9th May 2022) - Corsini, Christian; de Angelis, Mario; Villa, Luca; Somani, Bhaskar K.; Pietropaolo, Amelia; Montorsi, Francesco; Goumas, Ioannis Kartalas; Traxer, Olivier; Salonia, Andrea; Ventimiglia, Eugenio
Abstract : Purpose of review: Moses effect is an inherent physical principle of Ho:YAG laser functioning. Moses Technology is a pulse modulation modality of Ho:YAG laser, which became commercially available for the treatment of two urological conditions: urinary stones and benign prostatic obstruction. The purpose of this narrative review is to distinguish between Moses effect and Moses Technology, as well as to summarize the latest evidence on Moses Technology and its main application in the urological field. Recent findings: During laboratory lithotripsy, Moses Technology seems to reduce stone retropulsion and determine higher ablation volume compared with regular lithotripsy. However, this technology presents similar characteristics to long pulse Ho:YAG laser, and several studies showed no significant difference between Moses Technology and standard lasers. When used in prostate enucleation, Moses Technology promises to reduce operating time by increasing the efficiency of prostate resection and improve the hemostasis. Moreover, some studies state that it is possible to reduce the HoLEP morbidity. Despite this, the clinical impact of the time reduction remains uncertain and different studies either present relevant limitations or are burdened by significant bias. Summary: Although Moses effect has been extensively described and characterized, and several studies have been published on the usage of Moses Technology for both laser lithotripsy and laser enucleation of the prostate with Holmium YAG, solid clinical evidence on the real improvement of surgical outcomes is still missing.